Coal-based solid waste low-carbon cementitious material and low-temperature activation preparation method thereof
Patent Information
- Application Number
- CN202610880503.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-17
- Publication Date
- 2026-09-15
Smart Images

Figure CN122748990A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of solid waste resource utilization technology, and relates to a low-carbon cementitious material for coal-based solid waste and its low-temperature activation preparation method. Background Technology
[0002] Coal-based solid waste (such as fly ash, molten slag, furnace slag, and coal gangue) is a major industrial solid waste generated by coal-fired power generation and metallurgy, with huge annual emissions. Large-scale stockpiling not only occupies land resources but also causes serious pollution to water and soil environments. Preparing it into building cementitious materials is a technological path to achieve the resource utilization of major solid wastes, yielding significant economic and environmental benefits.
[0003] However, existing technologies for preparing coal-based solid waste cementitious materials have significant limitations in the following aspects: High energy consumption and large carbon emissions: Traditional processes must use a large amount of silicate cement clinker as the main cementing material, resulting in high energy consumption and large CO2 emissions, which contradicts the national "dual carbon" target.
[0004] Low solid waste content makes activation difficult: Due to the low early hydration activity of coal-based solid waste, the content of solid waste in traditional cementitious materials is usually less than 50%. Although conventional room temperature alkali activation process can improve the activity to a certain extent, the reaction is extremely slow and the early strength is extremely low; while high temperature calcination (≥800℃) or high pressure hydrothermal activation (≥150℃) can activate the activity, the energy consumption cost is extremely high and the equipment requirements are stringent, making it difficult to achieve industrial promotion.
[0005] Poor workability and volume stability: Existing cement-free alkali-activated systems generally suffer from problems such as extremely short setting time ("flash setting"), poor fluidity, easy shrinkage cracking, strength reduction and insufficient water resistance, which seriously limit their practical application in engineering.
[0006] There is an urgent need to develop a new type of low-carbon cementitious material that is completely free of cement, contains a high amount of solid waste, is activated at low temperature and low energy consumption, and has high early strength and controllable setting time. Summary of the Invention
[0007] To address the problems existing in the prior art, this invention provides a low-carbon cementitious material for coal-based solid waste and its low-temperature activation preparation method, thereby solving the significant limitations of existing coal-based solid waste cementitious material preparation technologies, such as high production energy consumption and carbon emissions, low solid waste content and difficulty in activation, and poor material performance and volume stability, which seriously restrict its large-scale and high-value application.
[0008] This invention is achieved through the following technical solution: A low-carbon cementitious material for coal-based solid waste includes solid powder and externally added water. By weight percentage, the solid powder comprises: Coal-based solid waste powder: 70%~85%; Slag powder 5%~15%; Compound alkali activator 3%~8%; Retarding and reinforcing composite agent: 0.3%~1.5%; The externally added water accounts for 12% to 20% of the weight of the solid powder.
[0009] Optionally, the coal-based solid waste powder is selected from one or more of liquid molten slag powder, fly ash, and slag powder.
[0010] Optionally, the coal-based solid waste powder is composed of liquid molten slag powder and fly ash, and the mass ratio of liquid molten slag powder to fly ash is (6~8):(2~4).
[0011] Optionally, the specific surface area of the coal-based solid waste powder is 350~500 m². 2 / kg, the specific surface area of the slag powder is ≥400m² 2 / kg.
[0012] Optionally, the composite alkali activator is composed of sodium silicate, sodium hydroxide and sodium carbonate, and the mass ratio of sodium silicate, sodium hydroxide and sodium carbonate is (2~4):(1~2):(0.5~1); the total modulus of the composite alkali activator is 1.0~1.6.
[0013] Optionally, the retarding and reinforcing composite agent is selected from one or more of sodium gluconate, triethanolamine, citric acid, and polycarboxylate superplasticizer.
[0014] Optionally, the retarding and reinforcing composite agent is composed of sodium gluconate and triethanolamine, and the mass ratio of sodium gluconate to triethanolamine is 1:(0.5~1).
[0015] The above-mentioned method for preparing a low-carbon cementitious material for coal-based solid waste includes the following steps: S1: Mix 70%~85% coal-based solid waste powder, 5%~15% slag powder, 3%~8% composite alkali activator, and 0.3%~1.5% retarding and reinforcing composite agent evenly according to weight percentage to obtain mixed powder; S2: Place the mixed powder in a heat preservation environment of 40~80℃ for 30~120min to activate it; S3: Add 12% to 20% by weight of external water to the activated mixed powder, stir to form a uniform slurry, inject into a mold to form, and finally cure to obtain the coal-based solid waste low-carbon cementitious material.
[0016] Optionally, in step S2, the activation temperature is 50~70℃ and the activation time is 45~90min.
[0017] The above-mentioned low-carbon cementitious material based on coal solid waste is used in precast building components, engineering grouting materials, mine filling binders, or road base stabilization materials.
[0018] Compared with the prior art, the present invention has the following beneficial technical effects: This invention discloses a low-carbon cementitious material based on coal-based solid waste. Through scientific component design and compounding technology, it systematically solves the technical bottlenecks of existing coal-based solid waste cementitious materials in terms of energy consumption, dosage, and performance. Addressing the problems of high energy consumption and large carbon emissions in production, this invention abandons traditional silicate cement clinker and constructs a complete solid waste cementitious system with 70%–85% coal-based solid waste powder and 5%–15% slag micro-powder. This eliminates the high-energy-consuming and high-emission cement production process at its source, significantly reducing the carbon footprint. Addressing the limitations of low solid waste dosage and difficulty in activation, this invention not only significantly increases the total solid waste dosage to over 85% but also introduces 3%–8% composite alkali activator. Utilizing the synergistic effect of chemical activation, it destroys the vitreous structure of solid waste, effectively solving the problems of low reactivity and difficulty in large-scale disposal of solid waste in conventional processes. To address the shortcomings of poor workability and volume stability in materials, this invention specifically adds 0.3% to 1.5% of a retarding and reinforcing composite agent. This component can precisely control the setting time of the slurry, effectively suppressing the "flash setting" phenomenon and shrinkage cracking risk common in alkali-activated materials, and significantly improving workability and volume stability. Furthermore, by strictly controlling the proportion of external water admixture at 12% to 20%, the hydration reaction environment is optimized, ensuring that the material achieves excellent mechanical strength and durability while realizing the disposal of high-level solid waste, thus truly realizing the large-scale, high-value utilization of coal-based solid waste.
[0019] Furthermore, the coal-based solid waste powder is selected from one or more of liquid slag powder, fly ash, and slag powder, which clarifies the specific source of the coal-based solid waste (liquid slag powder, fly ash, and slag powder), enhancing the feasibility and relevance of the technical solution. These materials are all typical low-activity coal-based solid wastes, proving the wide applicability of this invention to a variety of common coal-based solid wastes.
[0020] Furthermore, the coal-based solid waste powder is composed of liquid molten slag powder and fly ash, with a mass ratio of liquid molten slag powder to fly ash of (6~8):(2~4). By limiting the mass ratio of liquid molten slag powder to fly ash to (6~8):(2~4), the complementary activity and gradation of the solid waste components are achieved. Liquid molten slag typically has high potential hydraulic activity, while fly ash is mostly spherical particles, which can play a role in physical filling and lubrication. The specific ratio of the two can optimize the particle packing density and stimulate a synergistic cementing effect, thereby further improving the density and final strength of the material while ensuring a high solid waste content.
[0021] Furthermore, the specific surface area of the coal-based solid waste powder is 350~500 m². 2 / kg, the specific surface area of the slag powder is ≥400m² 2 / kg, limiting the specific surface area of coal-based solid waste powder to 350~500m² 2 / kg, slag powder ≥400m 2 / kg, by increasing the specific surface area through grinding, can significantly increase the contact area between solid waste particles and activators and water, effectively breaking down their surface inert layer and greatly enhancing their chemical reactivity. This is a key physical means to solve the problem of difficult activation of solid waste, laying the foundation for obtaining high early strength in the future.
[0022] Furthermore, the composite alkali activator is composed of sodium silicate, sodium hydroxide, and sodium carbonate, with a mass ratio of sodium silicate, sodium hydroxide, and sodium carbonate of (2~4):(1~2):(0.5~1). The total modulus of the composite alkali activator is 1.0~1.6, specifying that it is composed of sodium silicate, sodium hydroxide, and sodium carbonate in a specific ratio, and the total modulus is 1.0~1.6. This multi-component composite activation system is more effective than a single alkali activator: sodium hydroxide provides a strongly alkaline environment (OH-). - The activator rapidly disrupts the glassy structure; sodium silicate (water glass) directly provides silicate ions, promoting rapid gel formation through geological polymerization; sodium carbonate helps improve the fluidity and later strength development of the slurry. A specific modulus range ensures an optimal balance between the activator's reactivity and the slurry's workability.
[0023] Furthermore, the retarding and reinforcing composite agent is selected from one or more of sodium gluconate, triethanolamine, citric acid, and polycarboxylate superplasticizer, specifying the specific chemical composition of the retarding and reinforcing composite agent (such as sodium gluconate, triethanolamine, and polycarboxylate superplasticizer). These substances respectively play the roles of retarder, accelerator, and superplasticizer in the cementitious material. This limitation provides a concrete material basis for solving the common problems of flash setting and poor fluidity in alkali-activated materials, ensuring that the material has an adjustable setting time and good workability.
[0024] Furthermore, the retarding and strengthening composite agent is composed of sodium gluconate and triethanolamine, with a mass ratio of sodium gluconate to triethanolamine of 1:(0.5~1). Sodium gluconate mainly acts as a retarder, extending the workable time; while triethanolamine is a highly efficient early-strength agent. The synergistic combination of the two can precisely control the hydration reaction rate, avoiding flash setting while ensuring rapid early strength development, thus achieving a perfect balance between workability and mechanical properties.
[0025] This invention also discloses a method for preparing a low-carbon cementitious material based on coal-based solid waste, which has significant advantages in low carbon emissions, energy saving, and performance regulation. Firstly, in terms of process route, this method adopts a flow of dry mixing, followed by low-temperature thermal activation, and finally water addition and mixing. In particular, the low-temperature activation process at 40-80℃ in step S2 eliminates the high-temperature calcination step of traditional cementitious materials, allowing direct utilization of industrial waste heat or exhaust gas, significantly reducing production energy consumption and carbon emissions, and meeting the requirements of green manufacturing. Secondly, through the dry thermodynamic activation in step S2, the inert layer on the surface of coal-based solid waste particles can be effectively broken, overcoming its reaction energy barrier and significantly enhancing the potential activity of the solid waste. Therefore, after adding water in step S3, a rapid hydration reaction can occur, ensuring the material's excellent early strength. Furthermore, this method fully mixes the composite alkali activator and the retarding and reinforcing composite with the solid waste powder during the dry mixing stage. This not only avoids the flash coagulation phenomenon commonly seen in traditional alkali-activated materials and achieves precise control of the setting time, but also ensures the uniform distribution of each component at the microscale. The resulting cementitious material slurry has good fluidity, no bleeding, and high volume stability after hardening, perfectly solving the technical problem of poor construction performance of high-content solid waste materials.
[0026] Furthermore, in step S2, the activation temperature is 50~70℃ and the activation time is 45~90min. The activation temperature is further limited to 50~70℃ and the time to 45~90min. This is the optimal process window verified by experiments. Under these mild temperature and time conditions, the potential activity of coal-based solid waste can be maximized with minimal energy consumption, breaking down its energy barrier and enabling the material to rapidly acquire excellent early and late strength during subsequent curing, achieving the best balance between low energy consumption and high performance. Attached Figure Description
[0027] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0028] Figure 1 This is a flowchart of the preparation process of low-carbon cementitious materials for coal-based solid waste in this invention.
[0029] To enable those skilled in the art to understand the features and effects of the present invention, the terms and expressions used in the specification and claims are explained and defined in general below. Unless otherwise specified, all technical and scientific terms used herein have the ordinary meaning understood by those skilled in the art regarding the present invention, and in case of conflict, the definitions in this specification shall prevail.
[0030] The theories or mechanisms described and disclosed herein, whether right or wrong, should not in any way limit the scope of the invention, that is, the contents of the invention can be implemented without being limited by any particular theory or mechanism.
[0031] In this document, all features defined by numerical ranges or percentage ranges, such as numerical values, quantities, contents, and concentrations, are for the sake of brevity and convenience only. Accordingly, descriptions of numerical ranges or percentage ranges should be considered as covering and specifically disclosing all possible sub-ranges and individual numerical values (including integers and fractions) within those ranges.
[0032] In this article, unless otherwise specified, “contains,” “includes,” “containing,” “has,” or similar terms cover the meanings of “composed of” and “mainly composed of,” for example, “A contains a” covers the meanings of “A contains a and others” and “A contains only a.”
[0033] For the sake of brevity, not all possible combinations of the technical features in each implementation scheme or embodiment are described herein. Therefore, as long as there is no contradiction in the combination of these technical features, the technical features in each implementation scheme or embodiment can be combined arbitrarily, and all possible combinations should be considered within the scope of this specification.
[0034] This invention discloses a low-carbon cementitious material based on coal-based solid waste and its preparation method. This technology can completely replace traditional cement, and the total content of solid waste is not less than 70%. By adopting a low-temperature rapid activation process of 40~80℃, the prepared cementitious material not only has a controllable setting time, but also has excellent mechanical properties such as early strength and high strength, as well as good volume stability.
[0035] Specifically, a low-carbon cementitious material for coal-based solid waste comprises the following components by weight percentage: Coal-based solid waste powder: 70%~85%, selected from one or more combinations of liquid slag powder, fly ash, and slag powder, with a specific surface area controlled at 350~500 m². 2 / kg; Slag powder: 5%~15%, specific surface area ≥400m² 2 / kg; Composite alkali activator: 3%~8%, composed of sodium silicate, sodium hydroxide and sodium carbonate in a mass ratio of (2~4):(1~2):(0.5~1); Retarding and reinforcing composite agent: 0.3%~1.5%, selected from one or more of sodium gluconate, triethanolamine, citric acid, and polycarboxylate superplasticizer; Water: 12%~20% (external admixture ratio, percentage of the total weight of the above solid powder).
[0036] Further optimization, The preferred coal-based solid waste powder is a composite system of liquid molten slag powder and fly ash, with a mass ratio of (6~8):(2~4).
[0037] The preferred retarding and reinforcing composite agent is a mixture of sodium gluconate and triethanolamine in a mass ratio of 1:(0.5~1).
[0038] The total modulus of the composite alkali activator is controlled between 1.0 and 1.6.
[0039] This invention overcomes the bottlenecks of ineffective room temperature excitation and energy-intensive high temperature excitation. Its core mechanism lies in the synergistic effect of low-temperature thermodynamic excitation and multi-component composite chemical excitation. Low-temperature activation mechanism (40~80℃): Within this temperature range, the Si-O and Al-O bonds in the solid waste glass network structure are in a thermodynamically metastable state. The OH groups in the composite alkali activator... - Under moderate thermal energy, ions can quickly break the energy barrier of the glass depolymerization reaction, causing silicon-oxygen tetrahedra and aluminum-oxygen tetrahedra to rapidly depolymerize and dissolve, forming oligomers with gelling activity, without needing to reach the traditional high-temperature hydrothermal conditions above 100°C.
[0040] Composite activator mechanism: Sodium silicate provides the initial free silicon source, accelerating the nucleation of hydrated calcium silicate (CSH) gel; sodium hydroxide provides a strong alkaline environment, accelerating the depolymerization of the glass; sodium carbonate acts as a buffer and can react with calcium ions dissolved from solid waste to form calcium carbonate microcrystals, which act as crystal nuclei and fill pores, improving density.
[0041] Retarding and strengthening mechanism: Strong alkali activation easily leads to rapid setting. This invention uses sodium gluconate to form an adsorption film on the surface of hydrated particles, which delays network cross-linking; triethanolamine promotes early hydration of the aluminum phase, which compensates for the early strength loss caused by retarding and achieves a perfect balance between setting time and early strength.
[0042] like Figure 1 As shown, the present invention also discloses a method for preparing the aforementioned low-carbon cementitious material for coal-based solid waste, comprising the following steps: Raw material pretreatment: Crush and grind coal-based solid waste such as liquid slag powder and fly ash to a specific surface area of 350~500 m². 2 / kg, dried to a moisture content ≤1%; Metering and batching: Weigh out coal-based solid waste powder, slag powder, composite alkali activator, and retarding and reinforcing composite agent according to the set ratio; Dry mixing and homogenization: Put the above dry powder materials into a mixer and stir at room temperature for 5~15 minutes to obtain a uniformly mixed powder. Low-temperature activation: The mixed powder is placed in a heat preservation device at 40~80℃, preferably 50~70℃, and low-temperature dry activation is carried out for 30~120min, preferably 45~90min. This process can directly utilize the low-grade waste heat of power plants or steel plants. Add water and mix: Add the set proportion of external water to the activated mixed powder and stir vigorously for 3 to 8 minutes to form a uniform and fluid cementitious material slurry; when stirring vigorously here, the speed of the mixer should be set to 150 to 300 r / min.
[0043] Molding and Curing: The slurry is injected into a mold and cured under standard conditions at 20±2℃ and relative humidity ≥90% for 3~28 days; or a rapid curing process is adopted, which involves standing at room temperature for 2 hours, steam curing at 50~60℃ for 2~6 hours, and then standard curing to the specified age. Standard curing involves demolding the component after steam curing and transferring it to standard curing conditions (usually an environment with a temperature of 20±2℃ and relative humidity ≥90%) for continued curing. While steam curing can accelerate the material's formation, it may affect its long-term microstructure and final strength. Transferring to standard curing allows the material to continue hydrating in a stable environment, ensuring stable strength growth in the later stages and improving the material's durability and volume stability.
[0044] This invention possesses significant advantages in low-carbon environmental protection and resource recycling. In terms of environmental benefits, the material uses no silicate cement, the preparation process requires no high-temperature calcination, reducing production energy consumption by over 50% and carbon emissions by over 60%, achieving an extreme low-carbon goal. Simultaneously, its total content of coal-based solid waste and slag is as high as 85%~95%, greatly promoting the high-value-added, large-scale resource utilization of bulk industrial solid waste. In terms of process and performance, this technology only requires low-temperature activation at 40~80℃, can directly utilize industrial exhaust gas or waste heat, and the equipment is simple and easy for large-scale industrial production. The resulting material exhibits excellent mechanical and construction properties, with setting time that can be flexibly adjusted within the range of 30 to 180 minutes. It boasts extremely high early strength (3-day compressive strength ≥15MPa, 28-day compressive strength up to 45MPa or more), and is free from rapid setting and bleeding. It can directly replace traditional cement and is widely used in the preparation of precast building components, engineering grouting materials, mine backfill binders, or road base stabilization materials. It is applied in various engineering scenarios such as building materials, engineering grouting, mine backfilling, and road base.
[0045] In summary, this invention discloses a low-carbon cementitious material based on coal-based solid waste and its preparation method, belonging to the technical field of solid waste resource utilization and green building materials. The cementitious material comprises, by weight percentage: 70%–85% coal-based solid waste powder, 5%–15% slag powder, 3%–8% composite alkali activator, 0.3%–1.5% retarding and reinforcing composite agent, and 12%–20% externally added water. The preparation method includes raw material pretreatment, metering and batching, dry mixing and homogenization, low-temperature dry activation at 40–80℃ for 30–120 min, water addition and mixing, and molding and curing. This invention overcomes the bottlenecks of ineffective room-temperature activation and energy-intensive high-temperature activation, completely eliminating the use of cement and achieving extremely high coal-based solid waste content. The prepared cementitious material not only has low production energy consumption and low carbon emissions, but also possesses excellent properties such as high early strength, controllable setting time, no rapid setting, and volume stability, and can be widely used in building materials, engineering grouting, mine backfilling, and road base courses.
[0046] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.
[0047] The following examples use instruments and equipment conventional in the art. Experimental methods in the following examples, unless otherwise specified, are generally performed under conventional conditions or as recommended by the manufacturer. All raw materials used in the following examples are conventional commercially available products with specifications conventional in the art. In this specification and the following examples, unless otherwise specified, "%" refers to weight percentage, "parts" refers to parts by weight, and "ratio" refers to weight proportion.
[0048] Example 1 Raw material ratio: 85% coal-based solid waste powder (of which 85% is fly ash), 5% slag powder, 8% composite alkali activator (sodium silicate:sodium hydroxide:sodium carbonate=2:1.5:1), 1.5% retarding and reinforcing composite agent (sodium gluconate:triethanolamine=1:1), and external water added at 20% of the total powder.
[0049] Preparation process: Fly ash and slag powder are ball-milled to 350 μm. 2 / kg; mix dry powder according to ratio and stir for 10 min; place dry powder at 40℃ for 120 min to activate; add water and stir for 5 min; injection mold and cure under standard conditions of 20±2℃ and 95% relative humidity.
[0050] Example 2 Raw material ratio: 78% coal-based solid waste powder (52% liquid slag powder and 26% fly ash), 10% slag powder, 5.5% composite alkali activator (sodium silicate:sodium hydroxide:sodium carbonate = 3:1.5:0.8), 0.8% retarding and reinforcing composite agent (sodium gluconate:triethanolamine = 1:0.6), and external water added at 16% of the total powder.
[0051] Preparation process: The material is ball-milled to 450 μL. 2 / kg; stir for 10 minutes; place the dry powder at 60℃ for 60 minutes to activate; add water and stir for 5 minutes; mold and perform standard curing.
[0052] The ratio in this embodiment has the best effect.
[0053] Example 3 Raw material ratio: 70% coal-based solid waste powder (of which 60% liquid molten slag powder and 10% fly ash), 15% slag powder, 3% composite alkali activator, 0.3% retarding and reinforcing composite agent, and 12% external water.
[0054] Preparation process: The material is ball-milled to 500 μL. 2 / kg; stir for 5 minutes; place the dry powder at 80℃ for 30 minutes to activate; add water and stir for 3 minutes; pour into molds and cure according to standard.
[0055] Comparative Example 1 This comparative example does not undergo low-temperature activation and is prepared at room temperature, specifically as follows: The raw material ratio is exactly the same as in Example 2. However, in the preparation process, the "60℃ heat preservation activation" step is omitted. After dry mixing, water is added directly at room temperature (20℃) for mixing, molding and curing.
[0056] Comparative Example 2 The comparison example is for traditional cementitious materials. Raw material ratio: 30% fly ash, 70% P.O42.5 ordinary Portland cement, and 16% water. Mix at room temperature, form, and cure according to standard.
[0057] Test results and data comparison verification The performance of the cementitious materials prepared in the above embodiments and comparative examples was tested. The testing standards were in accordance with relevant national building material testing specifications (such as GB / T1346, GB / T17671, etc.). The test results are shown in Table 1.
[0058] Table 1 Comparison of performance test results between each embodiment and the comparative example
[0059] As shown in Table 1, this invention exhibits significant technical advantages in terms of low-temperature activation mechanism, feasibility of complete solid waste substitution, and control of construction performance. Firstly, the low-temperature activation process is key to improving material performance. Comparative data from Example 2 and Comparative Example 1 show that the 60℃ low-temperature activation technology of this invention effectively breaks the thermodynamic energy barrier of the solid waste vitreous body, causing its 3-day early strength to surge from 5.2 MPa to 24.3 MPa (nearly four times), and its 28-day strength to double, fully verifying the decisive role of this process in activating solid waste. Secondly, this invention confirms the feasibility of completely replacing cement. Under the stringent conditions of no cement clinker added and a total solid waste content as high as 88% (including 78% coal-based solid waste and 10% slag), the material's 28-day compressive strength reaches 47.5 MPa, not only surpassing the 42.6 MPa of the traditional cement system, but also demonstrating superior early strength performance, achieving a perfect balance between high solid waste content and high strength. Finally, addressing the flash-setting problem commonly found in traditional alkali-activated materials, this invention introduces a composite retarder and reinforcing agent system, successfully controlling the initial setting time within the range of 65-165 minutes. This completely solves the problem of an excessively short construction window, ensuring that the material can meet the practical application needs of various complex projects.
[0060] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.
Claims
1. A coal-based solid waste low-carbon cementitious material, characterized in that, Including solid powder and externally added water, the solid powder comprises, by weight percentage: Coal-based solid waste powder: 70%~85%; Slag powder 5%~15%; Compound alkali activator 3%~8%; Retarding and reinforcing composite agent: 0.3%~1.5%; The externally added water accounts for 12% to 20% of the weight of the solid powder.
2. The low-carbon cementitious material for coal-based solid waste according to claim 1, characterized in that, The coal-based solid waste powder is selected from one or more of liquid slag powder, fly ash, and slag powder.
3. The low-carbon cementitious material for coal-based solid waste according to claim 1, characterized in that, The coal-based solid waste powder is composed of liquid molten slag powder and fly ash, and the mass ratio of liquid molten slag powder to fly ash is (6~8):(2~4).
4. The low-carbon cementitious material for coal-based solid waste according to claim 1, characterized in that, The specific surface area of the coal-based solid waste powder is 350-500 m 2 / kg, and the specific surface area of the slag powder is ≥400 m 2 / kg.
5. The low-carbon cementitious material for coal-based solid waste according to claim 1, characterized in that, The composite alkali activator is composed of sodium silicate, sodium hydroxide and sodium carbonate, and the mass ratio of sodium silicate, sodium hydroxide and sodium carbonate is (2~4):(1~2):(0.5~1); the total modulus of the composite alkali activator is 1.0~1.
6.
6. The low-carbon cementitious material for coal-based solid waste according to claim 1, characterized in that, The retarding and reinforcing composite agent is selected from one or more of sodium gluconate, triethanolamine, citric acid, and polycarboxylate superplasticizer.
7. The low-carbon cementitious material for coal-based solid waste according to claim 1, characterized in that, The retarding and reinforcing composite agent is composed of sodium gluconate and triethanolamine, and the mass ratio of sodium gluconate to triethanolamine is 1:(0.5~1).
8. A low-temperature activation preparation method for a low-carbon cementitious material based on coal-based solid waste according to any one of claims 1 to 7, characterized in that, Includes the following steps: S1: Mix 70%~85% coal-based solid waste powder, 5%~15% slag powder, 3%~8% composite alkali activator, and 0.3%~1.5% retarding and reinforcing composite agent evenly according to weight percentage to obtain mixed powder; S2: Place the mixed powder in a heat preservation environment of 40~80℃ for 30~120min to activate it; S3: Add 12% to 20% by weight of external water to the activated mixed powder, stir to form a uniform slurry, inject into a mold to form, and finally cure to obtain the coal-based solid waste low-carbon cementitious material.
9. The low-temperature activation preparation method for a low-carbon cementitious material based on coal-based solid waste according to claim 8, characterized in that, In step S2, the activation temperature is 50~70℃ and the activation time is 45~90min.
10. The application of a coal-based solid waste low-carbon cementitious material as described in any one of claims 1 to 7 in precast building components, engineering grouting materials, mine filling binders, or road base stabilizing materials.